THE PRINCIPLE OF EQUALITY AND ITS EFFECTS ON THE MARITAL RELATIONSHIP AND ITS END WITHIN THE FRAMEWORK OF INTERNATIONAL LAW - Ammar Essa Kareem, Dawod Salman Abed, Nayif Ahmed Dhahi (Chelonian Research Foundation, 2023)
Our research topic deals with "the principle of equality and its effects on the marital relationship and its end within the framework of international law", and we mean here international law in its broad sense, i.e. international status covenants, to which are added the international provisions that came under Islamic international legislation. The problematic issue of this issue stems from the lack of a specific concept of the principle of equality and its scope within the framework of international law, as well as what are the effects that this principle can impose or have - in its positive and Islamic international concept - on marital relationship and its end?. In order to explain this specifically, we divided the research into an introduction and two requirements: First, to clarify the concept of the principle of equality within the scope of international law in a broad sense, and the second to define the effects of the principle of equality on the marital relationship and its end. The conclusion included an important number of results and recommendations in this regard, the most prominent of which are: The positive international law adopted the principle of equality in its absolute concept with everything related to marital relationship and its end, unlike international Islamic legislation, the principle of equality was adopted in its relative concept in the scope of marital relationship and its end. Both positive international law and international Islamic law have their justifications and arguments in support of this adoption.